Comparing the difference in traction between the bare hoof, iron horseshoes and two glue-on models on different surfaces - Siedler, C.; Zinkanel, Y. M.; Schramel, J. P.; Peham, C. (Sensors, 2025)
The interaction between equine hooves and various ground surfaces is a critical factor for injury prevention and performance in modern equestrian sports. Accurate measurement of surface grip is essential for evaluating the effectiveness of different hoof protection systems. This study introduces the Vienna Grip Tester (VGT), a novel sensor-based device developed to quantify rotational resistance—an important parameter for assessing hoof-surface interaction. The VGT utilizes a torque wrench and spring-loaded mechanism to simulate lateral hoof movements under a standardized vertical load (~700 N), enabling objective grip measurements across different conditions. Twenty combinations of hoof protection (barefoot, traditional iron shoe, and two glue-on models) and surfaces (sand, sand with fiber at 25 °C and -18 °C, frozen sand, and turf) were tested, yielding 305 torque measurements. Statistical analysis (repeated-measures ANOVA with Bonferroni correction) revealed significant differences in grip among surface types and hoof protection systems. Frozen surfaces (SDAF (31 ± 8.9 Nm and SDF 33 ± 8.7 Nm, p < 0.001) exhibited the highest grip, while dry sand (SDA (18.3 ± 3.3 Nm, p < 0.001) showed the lowest. Glue-on shoes (glue-on grip, 26 ± 10 Nm; glue-on, 25 ± 10 Nm) consistently provided superior grip compared to traditional or unshod hooves (bare hoof, 21 ± 7 Nm). These results validate the VGT as a reliable and practical tool for measuring hoof-surface grip, with potential applications in injury prevention, hoof protection development, and surface optimization in equestrian sports.